The Small Heart of Things : Being at Home in a Beckoning World - Hoffman, Julian (Book collections on Project MUSE., 2013)
In The Small Heart of Things, Julian Hoffman intimately examines the myriad ways in which connections to the natural world can be deepened through an equality of perception, whether it's a caterpillar carrying its house of leaves, transhumant shepherds ranging high mountain pastures, a quail taking cover on an empty steppe, or a Turkmen family emigrating from Afghanistan to Istanbul. The narrative spans the common--and often contested--ground that supports human and natural communities alike, seeking the unsung stories that sustain us. Guided by the belief of Rainer Maria Rilke that "everything beckons us to perceive it," Hoffman explores the area around the Prespa Lakes, the first transboundary park in the Balkans, shared by Greece, Albania, and the former Yugoslav Republic of Macedonia. From there he travels widely to regions rarely written about, exploring the idea that home is wherever we happen to be if we accord that place our close and patient attention. The Small Heart of Things is a book about looking and listening. It incorporates travel and natural history writing that interweaves human stories with those of wild creatures. Distinguished by Hoffman's belief that through awareness, curiosity, and openness we have the potential to forge abiding relationships with a range of places, it illuminates how these many connections can teach us to be at home in the world.